Diagnóstico dos impactos ambientais na área de proteção ambiental (APA) de Guaratuba, Paraná, Brasil - Kantek, Raphael Teles (2007)
The Atlantic Forest is a Brazilian ecosystem with high biodiversity and endemism. This research was conducted in the Environmental Protection Area, APA of Guaratuba (Guaratuba’s APA), and had as objective to get maps that provide data on environmental impacts. The methodology used was a combination of two instruments for collecting data. The first tool used was the Geographic Information System (GIS) and the second tool used was the Speech from the Collective Subject (DSC). The GIS is a geo-referenced tool that uses satellite images to generate maps. The five DSCs obtained through interviews, are the semiotic and cultural interpretation manual of the geographical object. Eight maps of Guaratuba’s APA were generated, containing information on the vegetation. From the generated maps 18 environmental impacts on the region were described, among them the roads are the most important, because through them the other impacts are facilitated. The data GIS has a detailed description of the geographic object, containing more situations that presented in DSC. Information obtained at GIS in general manner are the same data gotten with that on obtained from DSC. This duality of different origins in the data represents a holistic way as the research took place to offer suggestions to improve the condition’s existence to natural wildlife in the Guaratuba’s APA. The act of pressures way on the natural environment is complex and requires an analysis involving both the natural communities, as the human communities that live within the APA.